Neotectonic interpretations and PS-InSAR monitoring of crustal deformations in the Fujian area of China - Guo, Jianming; Xu, Shiyang; Fan, Hailong (Open Geosciences, 2017)
A neotectonic structural interpretation was conducted in the Fujian Province, west of the Taiwan Strait, by using computer image processing and 3D visualizations to enhance linear structural traces. The major faults in this area can be grouped into two conjugate shear fracture zones, with one trending to the northeast and the other trending to the northwest. PS-InSAR technology uses stable permanent target scatterer points to determine deformation rates and can effectively reduce the influence of spatiotemporal decorrelations and atmospheric anomalies that affect conventional D-InSAR techniques and prevent the formation of interference fringes. This study focuses on the fault zones located in the Quanzhou area of Fujian Province, where the 1604 M7.5–8.0 historic earthquake occurred. In total, 22 scenes of ERS SAR data from 1996 to 1999 were processed using PS-InSAR methods. The results show that the line of sight direction displacement rate of the main fault in the study area is 3–5 mm/yr, which indicates that the faults in this area are still active and subject to earthquake risk.